2019
DOI: 10.3390/su11082226
|View full text |Cite
|
Sign up to set email alerts
|

Engineering eHeritage—A New Approach for Study of Intangible Cultural Heritage. Case Study: The Analysis of the Noise Produced by the Dacian Dracon

Abstract: Preserving the past is an important task of the current generation because of the rapid changes that influence our society. There are certain objects or traditions that make us feel as though we are part of something and—a country, a way of life. The term ‘cultural heritage’ has seen many changes over the last decades and can be evaluated from a tangible or intangible point of view. Since the beginning of the 21st century, the recognition and protection of intangible cultural heritage (ICH) has seen an increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…Through the study of mobile crowdsourced cultural heritage, the article aims to promote the preservation and transmission of cultural heritage while providing guidance and support for related technologies and applications. The literature [15] takes a traditional musical instrument in Serbia, the vicious data dragon, as a case study and explores the application of digital engineering heritage in the study of intangible cultural heritage by analyzing its noise characteristics, examining the concept and technology of digital engineering heritage, analyzing its advantages and challenges in the study of intangible cultural heritage, and proposing some future research directions and application prospects. The literature [16] discusses the application of cultural heritage in educational programs and the role of place branding, using the case of the Smidurriwo and Golubac fortresses in Serbia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the study of mobile crowdsourced cultural heritage, the article aims to promote the preservation and transmission of cultural heritage while providing guidance and support for related technologies and applications. The literature [15] takes a traditional musical instrument in Serbia, the vicious data dragon, as a case study and explores the application of digital engineering heritage in the study of intangible cultural heritage by analyzing its noise characteristics, examining the concept and technology of digital engineering heritage, analyzing its advantages and challenges in the study of intangible cultural heritage, and proposing some future research directions and application prospects. The literature [16] discusses the application of cultural heritage in educational programs and the role of place branding, using the case of the Smidurriwo and Golubac fortresses in Serbia.…”
Section: Introductionmentioning
confidence: 99%
“…Shengnan Wu. Applied Mathematics and Nonlinear Sciences, 9(1) (2024)[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] …”
mentioning
confidence: 99%
“…A study of the intangible cultures of the three countries found that the display of rationality helps to encourage the safeguarding of intangible cultural heritage [20]. Butnariu, S. believes that the protection of ICH has become increasingly important since the 21st century, so he proposed a structured method for safeguarding intangible cultural heritage based on chip elements and made an empirical analysis of this type of case, which is very widely applicable in a wide range of fields, which promotes the innovation of intangible cultural heritage protection strategies [21].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, this is because most scholars study the inheritance and protection of national costume culture from the perspective of social science, and lack the application of information [9]. On the other hand, ethnic minorities have their own unique costume culture, and the workload of informatization based on the national costume image database is very large [10].…”
Section: Introductionmentioning
confidence: 99%